(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Patients with systemic lupus eythematosus (SLE) have increased susceptibility to infection by Pneumocystis jerovecii but this condition has rarely been reported in Bangladesh. Pneumonias due to Pneumocystis jerovecii commonly occur in immunocompromised hosts. Although it is a treatable infection, it is associated with high motility. Patient with systemic lupus erythomatosus increased susceptibility to infection by Pneumocystis jerovecii. Here we describe a patient with SLE who developed Pneumocystis pneumonia (PCP). A 37-years old female is a known case of SLE for 12 years admitted in BSMMU with the complaints of fever & cough for 3 months and breathlessness for 1 month. The patient is treated with corticosteroids and cyclosporine within 2months before presentation. Diagnosis is established based on the findings of induced sputum by Giemsa staining.This case demonstrates that PCP should be included in the differential diagnosis of patients of SLE presenting with pneumonic process. Bangladesh J Otorhinolaryngol; April 2015; 21(1): 57-59